(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2011)
In Voyous, Jacques Derrida develops his argument starting from the presupposition that democracy as such is the entity whose integrity and immunity are at stake and, therefore, under investigation. This gesture reflects the setting in which ten years before, in Foi et savoir, he had cast his reasoning about the logic of immunity. There, it was one of the sources of religion, the immunity of the sacred, that operated according to this logic. The hyphen between these two essays, beside Derrida’s own crossed references, is the genealogical reasoning on the meaning and essence of the concept of democracy: contrary to what Derrida claims, it will be maintained that Athenian democracy had a clear immune matrix, whose constant exercise is clearly defined, in spite of himself, by Vernant, and it will be shown how modern democracy has been forced to change policy. Modern democracy is an entity characterized by an immune deficiency. In order to save Derrida’s intuition from both the collapse of different vantage points and from a quite bizarre reticence in taking into account of the immune value of rituals, our starting point will be René Girard’s œuvre and his reading of the role of immune logic in sacred systems and, more generally, in modernity. The threshold between the auto-immune reaction, immune deficiency and auto-immune disease, between the sacrifice who delimits and constitutes the self and the holocauste du peuple en détail, is the space where, constantly exposed to the risk of auto-denial, democracy lives.